2014
DOI: 10.15290/ose.2014.05.71.12
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in the Position of Poland on Its Investment Development Path: the Results of the Empirical Analysis

Abstract: SummaryThe aim of this paper was to indicate on which stage of an economic development path is probably Poland. The subject of this paper was one of the economic development paths, named usually the investment development path, which model has been shaped mainly by J. H. Dunning and R. Narula. This model is also similar to the model of the economic development path proposed by M. Porter. Therefore, were discussed the changes in the main elements of this model, which took place in the Polish economy in 1995-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Among the Central and Eastern European countries, Poland has attracted most attention regarding empirical testing of the investment development path theory (Ciesielska & Frąszczak, 2014; Gorynia et al, 2008, 2019; Kosztowniak, 2019; Kuzel, 2017; Majewska & Buszkowska, 2014). Whilst Gorynia et al (2008, 2019) reported stage II, Kosztowniak (2019) and Kuzel (2017) reported early part of stage III.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the Central and Eastern European countries, Poland has attracted most attention regarding empirical testing of the investment development path theory (Ciesielska & Frąszczak, 2014; Gorynia et al, 2008, 2019; Kosztowniak, 2019; Kuzel, 2017; Majewska & Buszkowska, 2014). Whilst Gorynia et al (2008, 2019) reported stage II, Kosztowniak (2019) and Kuzel (2017) reported early part of stage III.…”
Section: Literature Reviewmentioning
confidence: 99%